2021
DOI: 10.1007/s13201-021-01486-2
|View full text |Cite
|
Sign up to set email alerts
|

Effective removal of Pb2+ from oral medical wastewater via an activated three-dimensional framework carbon (3D AFC)

Abstract: Oral medical wastewater with heavy metal ions (such as plumbum, Pb2+) is regarded as the main pollutant produced in the oral cavity diagnosis, and the treatment process can pose a serious threat to human health. The removal of Pb2+ from oral medical wastewater facing major difficulties and challenges. Therefore, it is of great significance to take effective measures to remove Pb2+ by using effective methods. A new activated three-dimensional framework carbon (3D AFC), regarded as the main material to remove Pb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
(38 reference statements)
1
1
0
Order By: Relevance
“…3c shows that, when the pH ranged from 1.3 to 9.3, the adsorption behavior of Pb 2+ on the NPC surface did not correlate with the ionic strength (0.001–0.005 mol L −1 ), and this result can be explained by the fact that the ionic valence state of Na + is lower than that of Pb 2+ 32. This result was consistent with formerly reported results 6, 33. It could also be inferred that the adsorption mechanism of Pb 2+ on the NPC surface was by inner surface coordination 34.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…3c shows that, when the pH ranged from 1.3 to 9.3, the adsorption behavior of Pb 2+ on the NPC surface did not correlate with the ionic strength (0.001–0.005 mol L −1 ), and this result can be explained by the fact that the ionic valence state of Na + is lower than that of Pb 2+ 32. This result was consistent with formerly reported results 6, 33. It could also be inferred that the adsorption mechanism of Pb 2+ on the NPC surface was by inner surface coordination 34.…”
Section: Resultssupporting
confidence: 90%
“…Pb 2+ is one of the primary heavy-metal contaminants. Jin et al [5] measured the leaching concentration of Pb 2+ in fly ash above 0.02 mg L -1 , and Song et al [6] found a Pb 2+ concentration in medical wastewater of 0.00835 mg L -1 . However, the World Health Organization (WHO) stipulates that the content of Pb 2+ in wastewater should be controlled below 0.01 mg L -1 [7].…”
Section: Introductionmentioning
confidence: 99%